2023
DOI: 10.1126/scitranslmed.abo3332
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with S pan , an antigen guided by SARS-CoV-2 S protein evolution, protects against challenge with viral variants in mice

Abstract: SARS-CoV-2 continues to accumulate mutations to evade immunity, leading to breakthrough infections after vaccination. How researchers can anticipate the evolutionary trajectory of the virus in advance in the design of next-generation vaccines requires investigation. Here, we performed a comprehensive study of 11,650,487 SARS-CoV-2 sequences, which revealed that the SARS-CoV-2 spike (S) protein evolved not randomly but into directional paths of either high infectivity plus low immune resistance or low infectivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…However, there are still several possible biases in this hypothesis, since the bat Sarbecovirus remains to be discovered, the cross-reactive immunity reported has not been tested so far for neutralization of SARS-CoV-2, and there is a huge difference between in vitro neutralization of a virus and in vivo protection of humans against this virus. There are still teams that seek to identify a variant-proof strategy for the development of a pan-betacoronaviruses vaccine formulation [ 38 , 171 , 172 , 173 ]. Additional hypotheses refer to as cross-reaction between dengue virus (DENV) antibodies and the SARS-CoV-2 S1 RBD [ 174 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are still several possible biases in this hypothesis, since the bat Sarbecovirus remains to be discovered, the cross-reactive immunity reported has not been tested so far for neutralization of SARS-CoV-2, and there is a huge difference between in vitro neutralization of a virus and in vivo protection of humans against this virus. There are still teams that seek to identify a variant-proof strategy for the development of a pan-betacoronaviruses vaccine formulation [ 38 , 171 , 172 , 173 ]. Additional hypotheses refer to as cross-reaction between dengue virus (DENV) antibodies and the SARS-CoV-2 S1 RBD [ 174 ].…”
Section: Discussionmentioning
confidence: 99%
“…They engineered seven broadly neutralizing antibodies that are highly effective against all tested variants of SARS-CoV-2, including XBB.1.5 and BQ.1.1. 55 Meanwhile, Zhao et al 56 designed a new pan-vaccine antigen (S pan ) based on the diverse evolution of SARS-CoV-2 spike sequences. It was found that S pan vaccination of mice elicited broad immunity to several variants, including Omicron BA.1.…”
Section: Strategies For Prevention Of Bq1 and Xbb Sublineagesmentioning
confidence: 99%
“…Recently, a pan-spike-protein-based vaccine was developed by investigating viral evolution and identifying spike protein consensus sequences that could elicit broadly neutralizing antibodies against circulating strains of the virus and possible future variants. However, further studies to evaluate the efficacy and durability of the immune response are required 10 . An optimal vaccine will ultimately combine innovations in antigen discovery and design with advances in adjuvants and vaccine formulation.…”
Section: News and Viewsmentioning
confidence: 99%